Parent preferences for telephone coaching to prevent and manage childhood obesity. Issue 1074 (26th March 2015) - Blaine, Rachel E; Pbert, Lori; Geller, Alan C; Powers, E Michael; Mitchell, Kathleen
ABSTRACT: Objective: To assess parent preferences for utilisation of a parent-focused, telephone-based coaching service, or 'FITLINE, ' to prevent or manage childhood obesity. Methods: A cross-sectional survey of parents of children aged 2–12 years was conducted at a paediatric practice in Greater Boston, Massachusetts, USA, between July 2012 and May 2013. Parents received questionnaires with clinic visit paperwork and opted-in to the study by returning them to clinic staff or by mail. The anonymous pen-to-paper questionnaire assessed parents' potential FITLINE utilisation, preferences regarding educational content and logistics, and parent/child demographics. Simple logistical regression was used to assess associations between parent and child factors and FITLINE interest. Results: Among n=114 participants, most parents reported being very likely (n=53, 48%) or somewhat likely (n=44, 40%) to use a FITLINE-promoting healthy habits for children if it was made available. Interest in a FITLINE was greatest among overweight or obese parents (OR 3.12, CI 1.17 to 8.30) and those with children aged <5 years (OR 2.42, CI 1.02 to 5.73). Parents desired to discuss their own health and fitness goals (84%) along with educational topics such as healthy food shopping on a budget (91%) and how to meet children's physical activity needs (81%). Most parents preferred to obtain a FITLINE referral from a paediatrician or nurse (73%), instead of a school nurse (42%) or child-care provider (26%). Conclusions: Given strong interest among parents in a FITLINE and the urgency of the youth obesity epidemic, implementation of a pilot phone-based service should be strongly considered.